Multimodal Semiotics of Theatrical Performances - Tan, Sabine; Wignell, Peter; O'Halloran, Kay (2016)
Introduction - This chapter adopts a multimodal social semiotic approach to exploring how various semiotic resources are exploited for meaning making in theatrical performances.